A Coupling Model for Tribodynamic Behavior of the Hydroviscous Flexible Drive With Consideration of Saucer-Warping Deformation. Issue 1 (2nd January 2023) - Cui, Jianzhong; Zhang, Dong; Xu, Yawen; Ma, Shunxi; Chen, Guitong
Abstract: An improved coupling model, including the dynamic transmission characteristics and thermal deformation behavior of the disks, is developed for predicting the tribodynamic behavior of the hydroviscous flexible drive under realistic driving conditions. The present work overcomes previous limitations by incorporating transient saucer-warping deformation due to friction heat. Dynamic parameters because of the saucer-warping angle effects, including the film thickness and total torque, are analyzed based on an iterative method. Axial deformation, radial deformation, and saucer-warping angle are simultaneously obtained by finite-element analysis. Based on the comparison with the experimental data, the performance of the coupling model is found satisfactory. The results show that the increase of the saucer-warping angle is favorable for the improvement of flexible transmission characteristics. As a result of the saucer-warping angle effects, significant reduction of the inlet flow rate will lead to the reduction of maximum total torque. Neither radial displacements nor axial displacements are good enough to predict the evolution rule about friction heat during the engagement process. Based on the combined effects of equivalent film thickness and real frictional area, the torque results for the deformed disks are larger than those when the disks are parallel. The saucer-warping angle effect begins to dominate the total torque especially when the film thickness reaches its minimum. The model developed in this research may become an efficient alternative model for the prediction of flexible transmission behavior of the real driving system.